Rainfall Analysis for Drought Estimation of Udaipur Region - Bhakar, S R; Bansal, A K; Chhajed, N; Singh, R V (Journal of Agricultural Engineering, 2006)
In regions where rainfall is erratic and frequent temporary drought conditions are expected within the monsoon season also, rainfall analysis for drought estimation is helpful for crop planning. In this paper normal, abnormal and drought months have been determined for the period of 1981-2005 of Udaipur region. Total 12 drought months were found during the rainy season in the duration of 1981-2005. Probability of occurrence of 6 drought months in a year was 96% and for 10 months was 4%.